Digital watermarking: A counterfeiting and piracy deterrence - Olanrewaju, Rashidah Funke; Khalifa, Othman Omran; Zeki, Akram M. (2012)
Counterfeiting and piracy are among substantial oldest problems associated with intellectual properties. With the advent of interconnected networks nowadays, the problems are expanding in scope and magnitude as well as increasing economic and social impact. The negative impacts of this development on associated industries and their employees have raised economic, health, safety and security concerns for both governments and consumers. Digital Watermarking (DW), an imperceptibly altering of host media to embed message or marks about the host itself can be effectively used to limit the scope of counterfeiting and piracy of digital media. This paper presents statistically, the extent of piracy and counterfeiting on digital media especially on software, music, e-books and pharmaceutical products. It also presents the current research finding and output of curbing piracy through the applications of watermarking to enhance owner's ability to detect and respond to misuse of digital media. The result of findings indicated that digital watermarking can help deter piracy and authenticate digital media extensively.